Evaluation of Water Resources Carrying Capacity in Liaoning Province Based on Entropy Weight TOPSIS Model - REN Bo; CAO Yongqiang; LI Kexin; YANG Xueting; ZHOU Shuhan; ZHAO Hui (Renmin Zhujiang)
Water resources are important for human survival.The utilization of water resources can influence the water cycle.At the same time,as an integral part of the hydrological cycle,water resources have a restrictive effect on the natural environment and human beings.In this paper,the relevant data on water resources,society,economy,and ecology from 2010 to 2020 were sorted out,and a multi-factor evaluation system was constructed.The weights were determined by combining the analytic hierarchy process and the entropy weight method.The ideal point method and a coupling coordination model were used to evaluate the water resources carrying capacity and the coordinated development level of each subsystem in Liaoning Province.In this way,it is expected to perfect the water resources management system and promote the development of water resources.The following results were obtained from this study.① The water resources carrying capacity of Liaoning Province showed an increasing trend during 2010—2020,and the carrying capacity was evaluated as grades Ⅱ—Ⅳ.② The coupling coordination level of water resources in Liaoning Province is between 0.6 and 0.9,which is in the transition stage from primary coordination to intermediate coordination.In 2020,all prefecture-level cities showed good coordination.The coupling coordination of water resources,society,economy,and ecology is in the order of economy>society>ecology>water resources.③ The water resources carrying capacity in Liaoning Province is mainly influenced by precipitation,sewage treatment rate,water resources volume,and the proportion of tertiary industry.In the future,we should improve water use efficiency,firmly establish the concept of green development,and realize the sustainable development of water resources.